Perception of unintentional childhood injuries among mothers in rural South India - Leeberk Raja Inbaraj; Anuradha Rose; Kuryan George; Anuratha Bose (Wolters Kluwer Medknow Publications, 2017)
Parental perception of safe and risk-free environment is critical in the prevention of unintentional childhood injury. In this cross-sectional study, hundred mothers from 13 clusters were interviewed to assess the perception of mothers regarding the risks and hazards leading to unintentional childhood injuries from March to April 2013. A tool developed by Glik et al. was used. Mothers' perception of likelihood of injury from hazards such as household door and drawers, small toys, plastic bags, and cribs was poor. Mothers had a poor perception of injury by entrapment in refrigerators, choking, and strangulation by a rope. Age, education, and literacy (P < 0.05) were found to be significant predictors of perception of risk and hazard. Very few mothers (9%) believed injuries can be completely prevented and illiteracy (P < 0.05) was associated with poor perception on prevention. Health education should focus on improving maternal perception which may bring positive impact on prevention.